Literature Review on Crowdsourcing for Local Tourism Development - Andaru, Fatah Mario; Puspitaningrum, Dika (INOVASI, 2025)
Global tourism has been shifting from a mass-market model toward an inclusive and sustainable approach that places local communities at the center of development. However, local tourism initiatives often face challenges such as fragmented governance, limited participation, and weak technological integration. This study aims to examine how crowdsourcing can serve as a participatory innovation mechanism that bridges these gaps by linking community-based tourism with knowledge and innovation management. Using a systematic literature review with a meta-synthesis approach, twelve international and national journal articles published between 2015 and 2025 were analyzed. The findings reveal that crowdsourcing not only facilitates the documentation and transfer of local knowledge but also transforms community wisdom such as traditions, narratives, and cultural practices into authentic tourism products. Digital platforms, including social media and blockchain systems, enhance transparency, collaboration, and equitable benefit sharing among community members. This study concludes that crowdsourcing functions as both a social and technological catalyst for inclusive tourism, enabling sustainable development through active community participation and digital empowerment.